The Use of Visual Picture in Increasing Students’ Writing Skill At the Ninth Grader of MTs NW No. 2 Rensing In the School Year 2022/2023 - Karomi Safari, M. Ubaidillah (khatulistiwa, 2022)
This study focused to know the effectiveness of using visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing. to what extent the effectiveness of using visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing. This was an experimental study. It consisted of two groups by 32 students divided into students as experimental and as control group. I used writing test in assessing students’ writing skill through visual picture and hypothesis testing. Result showed that mean score in pre-test and post-test for the experimental group was 60.56 and 65.13. Indeed, based on the result of hypothesis at the level of significance a = 0.05, I found that t-test > table were 5.18 > 2.048. Hypothesis was accepted. It means there was a significant effect of visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing in the school year 2022/2023.